Studi Kasus: Asuhan Keperawatan pada Pasien dengan Post Operasi Apendisitis (Case Study: Nursing Care In Patient with Post Operation Appendicitis) - Ardianti Dwi Lestari; Heru Supriyatno; Bambang Sarwono (Jurusan Keperawatan Mandiri Poltekkes Kemenkes Padang, 2023)
background: Appendicitis is inflammation caused by bacteria. Various factors that trigger the occurrence of appendicitis are the obstruction of the appendix lumen, lymphoid tissue hyperplasia, appendix tumors, ascaris worms, appendix mucosal erosion, and low-fiber diet which results in the appearance of appendicitis. Appendicitis is one of the most common causes of acute abdominal pain. Handling of appendicitis is by surgical operation of removal of the appendectomy. purpose: the purpose of this study was to determine nursing care in patients with postoperative appendicitis. method: the study uses descriptive methods using care studies through the nursing process approach. results: this study was conducted at Muntilan Publis Hospital in February 2019 in patient Ny. K collection is done by interviews, observation, physical examination, and documentation studies. Based on the study conducted, postoperative pain data obtained with a wound length of 10 cm, leukocytes 13.89 thousand/uL, temperature of 36.3°C. conclusion: in patient Ny. K obtained several nursing diagnoses that appeared, namely acute pain, and risk of infection.